2021
DOI: 10.1016/j.sjbs.2021.05.053
|View full text |Cite
|
Sign up to set email alerts
|

Potent antioxidant and anticancer activities of the methanolic extract of Calligonum comosum (L’Her) fruit hairs against human hepatocarcinoma cells

Abstract: Cancer is a devastating and aggressive disease that is globally ranked as the second-leading cause of deaths despite the relentless efforts being directed towards the discovery of novel chemotherapeutic drugs. Plants naturally produce a plethora of secondary metabolites that play a crucial role as effective therapeutic agents. Cancer treatment rely primarily on chemo- and radio-therapeutic strategies that suffers from known side effects. Recently, the strategy of controlling cancer progression by use of plant-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 25 publications
1
9
0
Order By: Relevance
“…Taken together, these results indicate that EECC inhibits growth of breast cancer cells, in part, by initiating apoptosis. These results are consistent with results of MTT assays ( Figure 1 ) and further validate previous reports that extracts of Calligonum comosum induce apoptosis in various in vitro human cancers ( Shalabi et al, 2015 ; Alehaideb et al, 2020 ; Alzahrani, 2021 ). Although slight but significant apoptosis was observed, necrotic cell death was far more profound.…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…Taken together, these results indicate that EECC inhibits growth of breast cancer cells, in part, by initiating apoptosis. These results are consistent with results of MTT assays ( Figure 1 ) and further validate previous reports that extracts of Calligonum comosum induce apoptosis in various in vitro human cancers ( Shalabi et al, 2015 ; Alehaideb et al, 2020 ; Alzahrani, 2021 ). Although slight but significant apoptosis was observed, necrotic cell death was far more profound.…”
Section: Discussionsupporting
confidence: 93%
“…It has been reported that Calligonum comosum exhibits antihyperglycemic activities, anti-inflammatory, anti-ulcer and anticancer activities in both rat and shrimp (El-Hawary and Kholief, 1990;Liu et al, 2001). In another study, Calligonum comosum exhibited both cytotoxicity and genotoxicity to human hepatocellular carcinoma (HepG2) cells (Shalabi et al, 2015;Alzahrani, 2021) and human triple-negative MDA-MB-231 breast cancer cells through the apoptotic pathway (Alehaideb et al, 2020). In HepG2 cells,extracts of Calligonum comosum have been reported to induce cytotoxicity through the apoptotic pathway (Shalabi et al, 2015;Alzahrani, 2021).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations